2008
DOI: 10.1200/jco.2007.10.8407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Response, Disease Control, Progression-Free Survival, and Time to Progression As Potential Surrogate End Points in Metastatic Breast Cancer

Abstract: BackgroundOverall survival (OS) can be observed only after prolonged follow-up, and any potential effect of first-line therapies on OS may be confounded by the effects of subsequent therapy. We investigated whether tumor response, disease control, progression-free survival (PFS), or time to progression (TTP) could be considered a valid surrogate for OS to assess the benefits of first-line therapies for patients with metastatic breast cancer. Patients and MethodsIndividual patient data were collected on 3,953 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
207
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 317 publications
(217 citation statements)
references
References 22 publications
5
207
0
5
Order By: Relevance
“…However, that meta-analysis appears to be unweighted. Our weighted analysis of anthracycline studies produced an R 2 value almost double that reported by Burzykowski et al (2008). Using sample sizes as weights, we show a moderately strong linear correlation between progression-free survival and survival, in a large group of studies covering many treatment types.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…However, that meta-analysis appears to be unweighted. Our weighted analysis of anthracycline studies produced an R 2 value almost double that reported by Burzykowski et al (2008). Using sample sizes as weights, we show a moderately strong linear correlation between progression-free survival and survival, in a large group of studies covering many treatment types.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, they found a stronger relationship between the end points in studies performed prior to 1990 when second-line therapies for metastatic cancer were not commonly used. More recently, a meta-analysis of 11 studies in (Burzykowski et al, 2008). The researchers found tumour response to be more highly associated with overall survival than was progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations between PFS or other endpoints and OS have been analyzed in an effort to identify surrogate endpoints of OS [10][11][12][13][14][15]. A validated shorter-term surrogate endpoint would likely both reduce drug development costs and facilitate the assessment of efficacy [16].…”
Section: Introductionmentioning
confidence: 99%